Successful Resection of Intracranial Metastasis of Hepatocellular Carcinoma - Okimoto, Kenichiro (S. Karger AG, 2013)
Intracranial metastasis of hepatocellular carcinoma (HCC) is rare, but has an extremely poor prognosis. We report a case with successful surgical removal of intracranial metastasis of HCC. A 32-year-old man was admitted to our hospital with severe vomiting. He had been followed for liver cirrhosis due to hepatitis B virus infection and received a right hepatic trisectionectomy for HCC 1 year earlier. For the recurrence of HCC, sorafenib had been administered 6 months before admission. On admission, he exhibited consciousness disturbance, which gradually worsened. Two days later, both computed tomography and magnetic resonance imaging revealed an intra-axial tumor with perifocal edema and hemorrhage in the left frontal lobe. The tumor was successfully removed by craniotomy and pathological examination revealed that it was composed of moderately differentiated HCC cells. The day after surgical resection of the tumor, his consciousness returned to normal. Subsequently, he was treated with hepatic arterial infusion chemotherapy with 5-fluorouracil and cisplatin using an implanted port-catheter system. Surgical resection of intracranial metastasis of HCC would be important and meaningful in some cases.